2019
DOI: 10.1177/0143034318822688
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of acculturative stress on refugee youth mental health: A systematic review and ecological approach to assessment and intervention

Abstract: In this article, we conduct a systematic review of the extant literature on the risk and protective factors that impact the healthy resettlement of refugee children around the world. We identify acculturative stress as a main risk factor to consider for assessment and intervention given that is often overlooked in the literature for refugee children, but has been found to strongly impact their socio-emotional development. In addition, we discuss ecologically framed/culturally responsive interventions and asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 40 publications
(114 reference statements)
1
46
0
1
Order By: Relevance
“…Similar to the current study's findings, Hyman et al (2000) highlighted Vietnamese refugee youths' feelings of frustration and estrangement in the classroom due to lack of academic language development and the inability to meet and communicate their level of academic competence and knowledge. Refugee youth resettled in other countries, like Australia and Canada, have reported similar challenges in learning their host country's language (d'Abreu et al, 2019). Regarding acculturation, Blanco-Vega et al (2008) identified acculturation gaps as a risk factor that often causes great stress to family systems, which may lead to negative outcomes among youth.…”
Section: Similarities With Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the current study's findings, Hyman et al (2000) highlighted Vietnamese refugee youths' feelings of frustration and estrangement in the classroom due to lack of academic language development and the inability to meet and communicate their level of academic competence and knowledge. Refugee youth resettled in other countries, like Australia and Canada, have reported similar challenges in learning their host country's language (d'Abreu et al, 2019). Regarding acculturation, Blanco-Vega et al (2008) identified acculturation gaps as a risk factor that often causes great stress to family systems, which may lead to negative outcomes among youth.…”
Section: Similarities With Previous Researchmentioning
confidence: 99%
“…Resettlement countries are faced with the challenge of understanding and meeting the needs of these families to effectively facilitate integration in their new society. Scholars have identified shared experiences among immigrant and resettled refugee youth, including adapting to a new political and social environment, encountering poverty, experiencing various mental health issues, and navigating acculturation gaps within family systems (Blanco-Vega et al, 2008;d'Abreu et al, 2019;Sua´rez-Orozco et al, 2018). Because refugees often have shared experience of resettlement and forced displacement, they may be viewed as a homogenous group of people, without regard for differences in religion, culture, refugee crisis, and level/type of trauma experienced prior to resettlement (Beiser et al, 2015).…”
mentioning
confidence: 99%
“…Within the last decade, there has been increased interest in investigating factors that could affect the mental health of young refugees' post-resettlement (Lau et al 2018;Sellars & Murphy 2018). A systematic review examining risk and protective factors affecting the health of refugee children resettled around the world identified acculturative stress as a main risk factor impacting their socio-emotional development (D'Abreu et al 2019). Other identified issues experienced by resettled young refugees include poor academic outcomes, ongoing trauma, settling into a new community, adapting to a different language and cultural systems, or coping with the loss of own sociocultural lifestyle (Albeg & Castro-Olivo 2014;Mulligan et al 2017).…”
Section: Resettled Young Refugees and Mental Healthmentioning
confidence: 99%
“…To date, 11 studies focusing specifically on the effect of acculturation in improving the mental health of young refugees resettled under the UNHCR humanitarian programme have been published. Seven studies were carried out in Australia (Correa-Velez et al 2010Earnest et al 2015;Gifford et al 2009;Kovacev & Shute 2004;McGregor et al 2016;McMichael et al 2011) and four in the United States of America (USA) (Betancourt et al 2015;D'Abreu et al 2019;Ellis et al 2010;Lincoln et al 2016). While Europe is one of the main areas of dispersal for UNHCR resettled refugees (United Nations High Commissioner for Refugees 2015), to date no studies are available from Europe, or the UK.…”
Section: Acculturation and Mental Healthmentioning
confidence: 99%
“…Firstly, a large proportion of existing reviews are conceptual and descriptive, with a limited focus to specific migrant issues, populations, or settings (Barrie & Mendes, 2011;Botfield, Newman, & Zwi, 2016;Connor, Page Layne, & Ellis Hilb, 2014;Demazure, Gaultier, & Pinsault, 2018;Ehntholt & Yule, 2006;Nocon, Eberle-Sejari, Unterhitzenberger, & Rosner, 2017;Streitwieser, Loo, Ohorodnik, & Jeong, 2018;Sullivan & Simonson, 2016;Tyrer & Fazel, 2014;Vossoughi, Jackson, Gusler, & Stone, 2018). Secondly, there are insufficient numbers of rigorously designed and executed systematic reviews that also include a transparently reported study quality appraisal (Borsch et al, 2018;Botfield, Newman, Lenette, Albury, & Zwi, 2018;d'Abreu, Castro-Olivo, & Ura, 2019;Nakeyar, Esses, & Reid, 2018;Van Os, Zijlstra, Knorth, Post, & Kalverboer, 2018). Thirdly, none of the reviews specifically examine whether interventions were co-designed and therefore incorporated stakeholder's views in the design of the study.…”
mentioning
confidence: 99%